Influencia de la estrategia didáctica "Figuricanto" en el desarrollo de la habilidad de Speaking del idioma Inglés en estudiantes del 5to grado "B" nivel primaria de la Institución Educativa José Enrique Celis Bardales, Tarapoto. San Martín-2011. - Muñoz Jimenez, Leydi Margoth (2013)
The present investigation work entitled: "lnfluence of the didactic strategy Figuricanto in the development of the speaking skill of the English language in students of the srn grade "B" primary level of the School José Enrique Celis Bardales Tarapoto-2011". lt is observad that inadequacy exists in the development of the skills of the English Language in the students. Sorne of the fundamental causes of this situation are a low writing and speaking level, insufficient and ineffective methodological didactic treatment of the audition of the English ianguage, low academic performance in the classroom and indifference to listen an interactiva class. The present study has as an objective to offer a didactic strategy which is guided to the developmept of the skill of the oral expression. The aleatory sampling was applied which is formed by 13 male and 17 female students, the type of the investigation is correlationaldescriptive. The following problem is proposed: How does the didactic strategy Figuricanto influence on the development of the Speaking skill of the English language? And the hypothesis the Didactic Strategy Flguricanto influences on the development of the Speaking skill of the English language in the students of the srn grade Bprimary level of the School José Enrique Celis Bardales Tarapoto-2011. It was determined that significant influence exists in the application of the didactic strategy Flgurlcanto in the development of the speaking skill of the English language with significance level of 5% and high correlation of 94.32%. Significant difference exists in the pre and a post test in the application of the Didactic Strategy Flguricanto at the significance level of 5% was determinad. In the post test, the average is 14.79 points and the percentage of students that are above this average is 51.92%. This average overcame the pre test in 126.1%; in this pre test, high variability exists and in the post test diminishes the variability where the seores spread to be homogeneous. The development of speaking skill of the English language the students is frequently carried out, 33% always and 7% almost always.